Pengaruh Pembelajaran PAK Menggunakan PAIKEM Terhadap Minat Belajar Peserta didik di SMA Taruna Mandiri Pamulang - May, May; Prasetya, Didimus Sutanto B. (STT Pelita Dunia, 2024)
Students lack interest in learning and tend to be monotonous because they do not clearly understand the teacher's teaching methods. Therefore, it is necessary to apply the PAIKEM method to increase students' interest in learning with a more creative and in-depth approach. This research uses descriptive methods combined with quantitative methods. The purpose is to measure the importance of the contribution of Christian religious education learning with PAIKEM method to students' learning enjoyment at SMA Taruna Mandiri Pamulang. The results showed that the effect of PAK learning with PAIKEM method simultaneously contributed 56.0% to students' learning interest, while the remaining 44.0% was influenced by other variables that were not in this study.